KADAR PROTEIN, KADAR KALSIUM, DAN KESUKAAN TERHADAP CITA RASA CHICKEN NUGGET HASIL SUBSTITUSI TERIGU DENGAN MOCAF DAN PENAMBAHAN TEPUNG TULANG RAWAN - Hanifa R. -; A. Hintono -; Y.B. Pramono - (Jurnal Pangan dan Gizi, 2013)
This study aims to determine the levels of protein, calcium levels, and preferences chicken nuggets were made ​​by substituting the use of Modified Cassava Flour (MOCAF) and the addition of bone flour. The analysis design of this research has been done  a completely randomized design with factorial. The treatments used in this study consisted of two factors, namely the substitution of wheat with Mocaf as factor A (A0 = 0%, = 10% A1, and A2 = 20%) and the addition of bone flour as factor B (B0 = 0%, B1 = 7.5%, and B2 = 15%). The first to make a chicken nuggets, after that test parameters, and data analysis using descriptic analysis and analysis of variance. The results showed an impact on the protein in the form of increased levels of the protein. Increased calcium levels occur with increases in bone flour used. In addition, no significant on flavor chicken nuggets.